Differential interaction of ADP-ribosylation factors 1, 3, and 5 with rat brain Golgi membranes. - Tsai, S C (1992)
Six mammalian ADP-ribosylation factors (ARFs) identified by cDNA cloning were expressed as recombinant proteins (rARFs) that stimulated cholera toxin ADP-ribosyltransferase activity. Microsequencing of soluble ARFs I and II (sARFs I and II), purified from bovine brain, established that they are ARFs 1 and 3, respectively. Rabbit antibodies (IgG) against sARF II reacted similarly with ARFs 1, 2, and 3 (class I) on Western blots. ARFs 1 and 3 were distinguished by their electrophoretic mobilities. Antiserum against rARF 5 cross-reacted partially with rARF 4 but not detectably with rARF 6 and minimally with class I ARFs. Guanosine 5'-O-(3-thiotriphosphate) (GTP[gamma S]) increased recovery of ARF activity and immunoreactivity in organelle fractions separated by density gradient centrifugation, after incubation of rat brain homogenate with ATP and a regenerating system. ARF 1 accumulated in microsomes plus Golgi and Golgi fractions, whereas ARF 5 seemed to localize more specifically in Golgi; the smaller increment in ARF 3 was distributed more evenly among fractions. On incubation of Golgi with a crude ARF fraction, GTP[gamma S], and an ATP-regenerating system, association of ARF activity with Golgi increased with increasing ATP concentration paralleled by increases in immunoreactive ARFs 1 and 5 and, to a lesser degree, ARF 3. Golgi incubated with GTP[gamma S] and purified ARF 1 or 3 bound more ARF 1 than ARF 3. Based on immunoreactivity and assay of ARF activity, individual ARFs 1, 3, and 5 appeared to behave independently and selectively in their GTP-dependent association with Golgi in vitro.